Presiones sobre el suelo: un panorama ecológico económico del sector agropecuario en Perú, 2000-2015 - Minaya Florez, Gretell Aurora (2022)
Given the development of the different streams of innovation in the agricultural sector worldwide, it is relevant to contrast the progressive vision of economic growth and increase in agricultural productivity with other holistic visions. These integral visions propose increasingly better tools that seek to emphasize human relationships with nature and, by this way, measure their socio-environmental effects and propose new forms of relationship. The following study presents the perspectives of innovation for the Peruvian agricultural sector and applies the Multi-Scale Integrated Analysis of Societal and Ecosystem Metabolism (MuSIASEM) which results show the sustainability of the sector, particularly an overview of soil degradation. This tool will provide a quantitative description of the pesticide and insecticide flows generated by agriculture in Peru and, in the same way, it will propose an explanation of their effects on the environment.